Neo-Aristotelian Naturalism as Ethical Naturalism - Moosavi, Parisa (Journal of moral philosophy, 2022)
Neo-Aristotelian naturalism purports to explain morality in terms of human nature, while maintaining that the relevant aspects of human nature cannot be known scientifically. This has led some to conclude that neo-Aristotelian naturalism is not a form of ethical naturalism in the standard, metaphysical sense. In this paper, I argue that neo-Aristotelian naturalism is in fact a standard form of ethical naturalism that is committed to metaphysical naturalism about moral truths and presents a distinctive and underappreciated argument for it. I reconstruct the neo-Aristotelian argument for ethical naturalism in terms of a continuity between the ethical domain and the natural domain of life. I argue that clarifying the meta-ethical import of neo-Aristotelian naturalism not only helps to situate it among other positions in meta-ethics, but also facilitates better critical engagement with the view.